Active Involvement of People with Dementia: A Systematic Review of Studies Developing Supportive Technologies - Suijkerbuijk, Sandra (J Alzheimers Dis, 2019)
Although there are promising benefits of supportive technology in dementia care, use of these technologies is still limited. It is challenging for researchers and developers in this field to actively involve people with dementia in development. This review updates and builds on existing knowledge by including a contemporary and relevant perspective. This perspective was gained by including search words and search databases from the field of Human Computer Interaction (HCI) and Design, as these fields were expected to supply novel insights in the complex task of actively involving people with dementia in developing supportive technologies. A total of 49 out of 3456 studies were included which describe the development of a great variety of technologies. Often people with dementia were involved in the generative or evaluative phase of the development. Interviews and observations were most commonly used methods. In seven articles the people with dementia were co-designers. This literature review reflects that people with dementia can influence the development of technology in regards to content, design, and even the initial idea, although the impact on how they experience their own involvement remains largely unknown. There is a lack of specific knowledge on appropriate methods and materials for active involvement of people with dementia in supportive technology development, even when including articles from the field of HCI and Design. Future research is needed to further appreciate and improve the desired role of people with dementia in meaningful technology development.